Uncovering the Relationship Between Audit Opinion, Financial Performance on Firm Value. - Ulfa, Yessy Naila; Rahmawati; Junaid M.Shaikh (Riset Akuntansi dan Keuangan Indonesia, 2026)
This study examines the relationship between financial performance, audit opinions, and firm value, with a focus on understanding how audit opinions mediate this relationship. Drawing on a sample of firms listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the proposed relationships. The findings reveal that while financial performance does not directly impact firm value, it is strongly positively associated with audit opinions, suggesting that better financial performance reduces agency risks and increases the likelihood of favorable audit outcomes. Audit opinions, in turn, are significantly associated with firm value, highlighting their role in enhancing investor confidence and the credibility of financial information. However, the mediating role of audit opinions in the relationship between financial performance and firm value was determined to be statistically insignificant, indicating that other factors also contribute to firm valuation. The study concludes that both financial performance and audit opinion significantly influence firm value, emphasizing the importance of considering both financial and non-financial factors in corporate valuation. The findings underscore the complexity of firm value determinants and provide insights into the interplay between financial performance, audit opinions, and market valuation in emerging markets.